Factors affecting the library usage patterns of the undergraduate students of the UP College of Architecture - Galora, Huwaran Mapalarin Sinag C.; Lapuz, Elvira B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2006)
Students experience and use the college library. Their perceptions and assessment regarding the improvements of the college library are two factors that must be recognized as a gauge of determining the efficiency of its services. That is why the students are chosen in this study as respondents to be able to help in assessing the college library of the UP College of Architecture. The study attempted to determine the library usage patterns of UP College of Architecture students. Specifically, it sought to know the factors that influence their library usage patterns. It also aimed to know their evaluation of the library's resources, facilities and services. Lastly, it sought to show the significant relationship between the library resources, facilities and services, and the library usage patterns of the architecture students.
The survey method was used in gathering the necessary data for the study. Survey questionnaires were distributed to the undergraduate architecture students who enrolled in the first semester AY 2006-2007. Convenience sampling was used in gathering the data. The data gathered were tabulated and analyzed using the Statistical Package for the Social Science (SPSS), using frequency and percentage distribution. Pearson correlation was used to test the significant relationship of the respondents' personal attributes, architecture research need; and the library's resources, services and facilities as related to the users' library usage patterns.
A total of 238 questionnaires was distributed and 221 or 92.9 percent were retrieved. The students evaluated the resources, facilities, and services of the UP College of Architecture Library and the results of the survey show that the library can sustain the architecture research needs of the undergraduate students of the UP College of Architecture. The results also show that majority of the undergraduate architecture students used the UP College of Architecture Library several times a week with a frequency of 84 or 38.0 percent. The results also revealed that the library staff are helpful and effective with frequency of 94 or 42.5 percent; the independent variables such as the architecture research needs and the library resources and facilities have a significant relationship with the users' library usage patterns. The UP College of Architecture provides quality library resources, facilities and services. Although there are some negative comments, the library as a whole, can sustain the needs of the students. The negative observations of the respondents are only minor problems that must be considered in improving the library resources, facilities, and services of the library. In order to achieve this, some recommendations were formulated such as: a more extensive library service; more models, drawings, and sculptures should be considered; and more updated books should also be acquired.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines. College of Architecture Library; College students -- Philippines -- Quezon City; Library use studies -- Philippines -- Quezon City